2004
DOI: 10.1111/j.1468-3148.2004.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Risk Assessment and Management System: An Assessment of Immediate Risk of Violence for Individuals with Offending and Challenging Behaviour

Abstract: Purpose Research on dynamic risk assessment has developed over the last 10 years and a number of variables have emerged as being possible predictors of future sexual and violent offences. These variables include hostile attitude/anger and compliance with routine. In 2002, Thornton (Sexual Abuse: A Journal of Research & Treatment 14, 139) developed a framework for dynamic risk assessment which also includes distorted and dysfunctional attitudes, socio-affective functioning, self-management and, for sex offender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Although static risk factors such as personal demographic and criminal history variables are robust predictors, particularly over the long term, there are data to suggest that dynamic risk factors that are also prominent clinical features of mentally disordered and learningdisabled offenders can be identified, shown to change over short time periods (Lindsay et al, 2004), and found to predict elopement and criminal recidivism (Quinsey, Coleman, Jones, & Altrows, 1997). This is of considerable importance in secure settings where the principle focus of violence risk assessments is the more immediate timeframe rather than years after transfer and release, and where the aim is to identify targets that might be amenable to intervention in order to lower the risk of violence.…”
Section: The Needs Principlementioning
confidence: 97%
“…Although static risk factors such as personal demographic and criminal history variables are robust predictors, particularly over the long term, there are data to suggest that dynamic risk factors that are also prominent clinical features of mentally disordered and learningdisabled offenders can be identified, shown to change over short time periods (Lindsay et al, 2004), and found to predict elopement and criminal recidivism (Quinsey, Coleman, Jones, & Altrows, 1997). This is of considerable importance in secure settings where the principle focus of violence risk assessments is the more immediate timeframe rather than years after transfer and release, and where the aim is to identify targets that might be amenable to intervention in order to lower the risk of violence.…”
Section: The Needs Principlementioning
confidence: 97%
“…For example, the HCR-20 considers romantic and intimate relationships to assess an individual's ability to form and maintain stable relationships (Webster et al, 1997). One limitation of this item for ID offenders is that reportedly as few as 2% of male ID offenders have experienced intimate relationships, possibly due to a Downloaded by [Computing & Library Services, University of Huddersfield] at 22:06 26 December 2014 lack of opportunity to develop such relationships, not inability to develop stable relationships (Lindsay et al, 2004, cited in Boer et al, 2010. For an ID population, the ID Supplement recommends other forms of social relationships should be considered to assess stability to reduce false-positive assessments of risk (Boer et al, 2010).…”
Section: Id Supplementmentioning
confidence: 97%
“…While one study did explore ID offenders in the community, idiosyncratic changes were made by the authors to the HCR-20 scoring criteria, which may have limited generaliszbility of the results and influenced the reliability of scoring (Boer et al, 2010). Despite increased research on ID offenders, the lack of standardization in this research leaves many questions unanswered about the risk factors for violence for this population (Boer et al, 2010;Lindsay et al, 2004).…”
Section: Id Supplementmentioning
confidence: 99%
“…Autor ističe značaj neadekvatnog socioafektivnog funkcionisanja kao prediktivnog faktora, naročito hostilnosti i agresivnosti, kao i siromašnih socijalnih veza i nedostatka bliskosti sa primarnom porodicom. Komentarišući rezultate istraživanja Lindzija i saradnika (Lindsay et al, 2004, prema Lindsay, 2012, koje se bavilo prediktivnim značajem različitih varijabli na uzorku od 52 seksualna prestupnika sa IO, od kojih je 18 recidivista i nakon tretmana, Lindzi navodi da su najjaču prediktivnu vrednost imale sledeće varijable: antisocijalni stavovi, nisko samopoštovanje, tolerantni stavovi prema seksualnim zločinima, niska motivacija za tretman, dozvole od strane osoblja i nedostatak bliskosti s majkom.…”
Section: Prevalencija Seksualnog Prestupništva Kod Osoba Sa Iounclassified
“…Među instrumentima za procenu dominiraju oni koji detektuju dinamičke faktore rizika, stabilne (seksualna interesovanja, stavovi, problemi samokontrole i samousmeravanja) i fluktuirajuće (zloupotreba psihoaktivnih supstanci, raspoloženje), zbog toga što su oni podložni promeni i što se tretmani i zasnivaju upravo na uticanju na dinamičke faktore rizika (Thornton, 2002). Primer jednog od takvih instrumenata, koji je namenjen određivanju dinamičkih prediktora prestupničkog ponašanja, jeste Sistem za procenu dinamičkog rizika i kontrole (Dynamic Risk Assesment and Management System -DRAMS), kojim se procenjuju stabilni dinamički faktori (samoregulacija, intruzivne seksualne misli, emocionalne veze) i akutni dinamički faktori (antisocijalno ponašanje, zloupotreba supstanci, pristup žrtvi, seksualno neadekvatno ponašanje) (Lindsay et al, 2004).…”
Section: Procena Seksualnog Prestupništva Kod Osoba Sa Iounclassified